PENYAKIT KULIT PADA PEKERJA PENYAMAKAN KULIT DI DESA MOJOPURNO KECAMATAN NGARIBOYO KABUPATEN MAGETAN TAHUN 2015 - Lathiefah Ekawati; NurHaidah .; Marlik . (Poltekkes Kemenkes Surabaya, 2015)
Leather tanning is an industry that processes raw hides into finished leather. This process useschromium. Chromium will be in contact with workers’ skin. The purpose of this study is to describeskin disease in tanning workers in Mojopurno Village, Sub District of Ngariboyo, Magetan 2015.This is a descriptive study conducted by illustrating skin diseases in tanning workers. Thedescription of skin diseases in the study includes characteristicsof skin disease, knowledge,attitudes and actions of workers as well as environmental factors. The population of this study wastanning workers of Mojopurno Village, Magetan.The result shows that there were 24 out of 103 workers who suffered from skin problems. Most ofthe sufferers were 41-50 years of 41.6%. Exposure duration with Chromium was ≥ 8 hours / dayof 95.8% with doses of Chromium of 80 mcg / m3. 12.5% of the sufferers possessed history ofallergy to chemicals. 54.2% Suffererspossessed fairly good knowledge on occupational skindiseases. 100% sufferers performed good attitude and 66.7% sufferers performed good action.Work environment (temperature, humidity and ventilation) in the leather tanning of Mojopurno Village, Magetan have qualified. Home Industry owners are advised to provide education on health and safety at work particularlyonoccupational disease, provideand enforce policies in the use the equipment. Workers areexpected to always usecomplete Personal Protective Equipment (PPE). Community around Leathertanning Home industry should submit suggestions and complaints to the owner of Home Industry.